Utilization of Parallel Resources and Sociodemographic Factors in Treating Children with Complex Chronic Diseases: A Cross-Sectional Study - Bibiana Pérez-Ardanaz; María José Peláez-Cantero; María González-; Laura Gutiérrez-Rodríguez; Alberto José Gómez-González; Inmaculada Lupiáñez-Pérez; José Miguel Morales-Asencio; José Carlos Canca-Sánchez (MDPI AG, 2021)
Background: Children with complex chronic conditions have a high need for health and social care resources. Many parents explore parallel resources such as alternative therapies, associations, psychological support, private medical consultations, and other out-of-pocket expenses for healthcare. The use of these alternative health resources is sometimes unclear and may lead to health inequalities. To characterize the use made of alternative healthcare resources for children with complex chronic conditions. Additionally, we evaluate the influence of sociodemographic factors on the distribution of this utilization of resources; (2) Methods: Cross-sectional study. Children with complex chronic diseases were treated at a tertiary hospital in Granada, Spain in 2016. We analyzed their use of healthcare resources and socioeconomic variables. This research complies with STROBE guidelines for observational studies; (3) Results: In total, 265 children were analyzed (mean age 7.3 years, SD 4.63). A total of 105 children (39.6%) attended private consultations with specialists, and 12.1% (n = 32) of the children had additional private health insurance. One out three parents belonged to a mutual support association (n = 78), and 26% (n = 69) of the children used alternative therapies. Furthermore, 75.4% (n = 199) of the children received no psychological support. Children whose parents had a higher educational level and occupations status made greater use of parallel healthcare resources.; (4) Conclusions: A significant proportion of children used multiple health resources in addition to the public healthcare system depending on sociodemographic determinants. Studies are needed to determine whether the use of these alternative services achieves better levels of health.